Características de la relación de pareja establecida por personas que Culminaron su Vínculo Afectivo en Tiempos de Pandemia COVID 19 (2023)
The main objective of this study was to analyze the relationship characteristics of couples who culminated their affective bond in times of pandemic, through qualitative research of a narrative type under a systemic theoretical approach, using the open interview instrument applied to four participants, two men and two women between the ages of 25 and 40 from the city of Bogotá.